Parenting under pressure: a cross-sectional questionnaire study of psychological distress, parenting concerns, self-efficacy, and emotion regulation in parents with cancer - Maria Romare Strandh; Pia Enebrink; Karin Stålberg; Renita Sörensdotter; Lisa Ljungman; Anna Wikman (Acta Oncologica, 2024)
Background and purpose: As many as one in four adults with cancer have children under 18 years.